Potensi Limbah Pertanian dan Perkebunan sebagai Sumber Pakan Ternak Ruminansia Berdasarkan Daya Dukung Nutrisi (BK, PK, dan TDN) di Kabupaten Paser, Kalimantan Timur - Nurjannah, I; Fanani, A F (Politeknik Negeri Lampung, 2026)
Paser Regency in East Kalimantan Province has considerable potential in the agricultural and plantation sectors, which generate substantial amounts of biomass residues that can be utilized as alternative feed resources for ruminant livestock. However, quantitative evaluations of the contribution of these residues to regional feed availability remain limited. This study aimed to assess the potential of agricultural and plantation residues as sources of ruminant feed in Paser Regency based on the availability of dry matter (DM), crude protein (CP), and total digestible nutrients (TDN), as well as to estimate the regional feed carrying capacity. This research employed a descriptive quantitative approach using secondary data obtained from the official publication